A rare case of angiosarcoma with skull masses and erythropenia and thrombocytopenia: A case report and review of literature. Issue 49 (December 2017) - Gao, Liansheng; Xu, Weilin; Li, Tao; Luo, Huali; Gai, Shiying; Xing, Ruxin; Chen, Gao; Chen, Yili
Abstract: Rationale: Primary splenic angiosarcoma (PSA) is a rare, fatal neoplasm originating from sinusoidal vascular endothelial cells, and usually metastasizes and almost always has a poor prognosis. Surgical excision is the main treatment of this highly malignant disease. Patient concerns: We reported a special case of a 68-year-old female who had a 6-month history of scalp masses. Diagnosis: The patient was found to have 2 skull masses on computed tomography (CT). Laboratory findings revealed erythropenia and thrombocytopenia. Enhanced abdomen magnetic resonance imaging (MRI) showed multiple masses in liver and spleen. The pathological result of the skull masses was revealed to be metastatic angiosarcoma. Interventions: The patient underwent surgical excision of skull masses, and no subsequent radiotherapy or chemotherapy was done. Outcomes: The patient died due to dyscrasia at August 12, 2015, with a survival of nearly 1 month. Lessons: We highlight the importance for clinicians to be aware of this rare neoplasm, and to consider it in the differential diagnosis when encountering a skull mass. Early confirmation and treatment may improve the prognosis.